Perbedaan kualitas daging ayam broiler ditinjau dari perubahan nilai pH dan daya ikat air di Pasar Oeba dan Pasar Naikoten Kota Kupang - Marlin Erlinda Manufoe; Diana A. Wuri; Annytha I.R. Detha (Jurnal Veteriner Nusantara, 2019)
Broiler is type of chicken resulted from cross-breeding, selection and genetic engineering from chicken species with high meat productivity. Broiler meat is nutritious, tasty, savory, and tender texture despite its relatively expensive, making this type of meat is consumed by almost any class of society. therefore, it is important to determine the quality of broiler meat. Parameters that can determine the quality are pH and water holding capacity (WHC). The purpose of this research was to compare the quality of chicken broiler meat obtained in Oeba market and Naikoten market, Kupang City with pH measurement in 1 hour, 6 hours, and 24 hours postmortem and water holding capacity (WHC) measurement. The number of samples are 72 samples consisted of 39 samples from Oeba market and 33 others from Naikoten market. Results showed that in Oeba market 41,03% samples of meat indicated good quality, 58,97% samples had DFD quality with average cooking loss rate 27,85% and high WHC. Meanwhile, in Naikoten market it is shown that 60,66% samples had good quality, and 33,34% with average cooking loss rate 30,45% and low WHC. From the result, it can be concluded that chicken broiler from Naikoten market had better quality than any chicken broiler from Oeba market.